Composite magnetostrictive materials for advanced automotive magnetomechanical sensors - McCallum, R. W.; Dennis, K. W.; Jiles, D. C.; Snyder, J. E.; Chen, Y. H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
In this paper we present the development of a composite magnetostrictive material for automotive applications. The material is based on cobalt ferrite, CoO×Fe2O3, and contains a small fraction ofmetallic matrix phase that serves both as a liquid phase sintering aid during processing and enhances the mechanical properties over those of a simple sintered ferrite ceramic. In addition the metal matrix makesit possible to braze the material making the assembly of a sensor relatively simple. The material exhibits good sensitivity and should have high corrosion resistance while at the same time it is low cost.